Immunohistochemical markers for tumor associated macrophages and survival in advanced classical Hodgkin’s lymphoma - Beatriz Sánchez-Espiridión; Ana M. Martin-Moreno; Carlos Montalbán; L. Jeffrey Medeiros; Francisco Vega; Anas Younes; Miguel A. Piris; Juan F. Garcia (Haematologica, 2012)
A subset of patients with advanced classical Hodgkin’s lymphoma is refractory to standard therapies. Therefore, it is relevant to identify new biologically-based prognostic markers. Recently, tumor associated macrophages have been proposed as a factor that predicts survival, although contradictory results have also been reported.Here we analyzed four macrophage markers (CD68, CD163, LYZ, and STAT1) using immunohistochemistry and automated quantification, in two independent series of advanced classical Hodgkin’s lymphoma (n=266 and 103 patients, respectively).Our results did not confirm that specific macrophage immunohistochemical markers could be used as surrogates for gene expression profiling studies. Survival analyses did not show correlation between CD163, LYZ or STAT1 and either failure-free or disease-specific survival. There was an association between CD68 and disease-specific survival, but it was not consistent in both series.In conclusion, individual tumor associated macrophage markers cannot be used to predict outcome before technical standardization and prospective validation in independent series of patients with comparable stages and treatments.